Comparison of Exponential Moving Average and Brown's Double Exponential Smoothing Method for Forecasting Glass Craft Sales - Ruli Utami; Kelvin Dwi Pratama; Suryo Atmojo (Procedia of Engineering and Life Science, 2022)
Glass crafts are one of the MSME products in Indonesia, in selling process transactions there’re many inconsistent between the available stock and the agreed transactions number. This will have a significant impact on customer trust which will lead to a reduction purchases number. So the researchers took the initiative to make sales forecasts to predict next sales number, due to the many forecasting methods available, the researchers will use two methods which will be compared to find out the most effective method for forecasting sales number. From the forecasting calculations using the exponential moving average method and the Brown's double exponential smoothing method, it can be concluded that the best method used in calculating sales forecasting for glass craft products at MSMEs is the Brown's Double Exponential Smoothing method using α value of =0.5 which produces MAPE is 3.19% and the next sales forecast value (January 2021) is 6.33.